2020
DOI: 10.1101/2020.10.06.327742
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cytoplasmic short linear motifs in ACE2 and integrin β3 link SARS-CoV-2 host cell receptors to endocytosis and autophagy

Abstract: The spike protein of the SARS-CoV-2 interacts with angiotensin converting enzyme 2 (ACE2) and enters the host cell by receptor-mediated endocytosis. Concomitantly, evidence is pointing to the involvement of additional host cell receptors, such as integrins. The cytoplasmic tails of ACE2 and integrin β3 contain a plethora of predicted binding motifs. Here, we confirm the functionality of some of these motifs through affinity measurements. The class I PDZ binding motif in the ACE2 cytoplasmic tail binds the firs… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 64 publications
1
26
0
Order By: Relevance
“…S3) indicates that this motif instance has an even earlier evolutionary origin than the origin of ACE2 itself, hinting at a key role in internalization. As expected, because the specificity is not yet defined, Dab1 and four other tested PTB domains did not bind to the ACE2 tail region (48). A poorly soluble sorting nexin 17 (SNX17) FERM domain was found to bind with ≈100 M affinity, providing an ambiguous result.…”
Section: Proteinmentioning
confidence: 66%
See 3 more Smart Citations
“…S3) indicates that this motif instance has an even earlier evolutionary origin than the origin of ACE2 itself, hinting at a key role in internalization. As expected, because the specificity is not yet defined, Dab1 and four other tested PTB domains did not bind to the ACE2 tail region (48). A poorly soluble sorting nexin 17 (SNX17) FERM domain was found to bind with ≈100 M affinity, providing an ambiguous result.…”
Section: Proteinmentioning
confidence: 66%
“…Thus, the mammalian ACE2, which internalizes the coronavirus, has a SLiM candidate for internalization appropriately located within its cytosolic tail. The ACE2 tail sequence was found to bind with moderate affinity to AP2 μ2 subunit ( 48 ) well within the 30 to 100 μM range of biologically relevant affinities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They found conserved motifs on the cytoplasmatic tails of ACE2 and integrin β3 that interacts with several critical regulatory protein domains. This motif information was tested later on experimental binding affinity measurements [ 19 ] and found that NHERF3 PDZ1, SHANK1 and SNX27 PDZ domains bind to synthetic peptides of the ACE2, and to the synthetic ATG8 domains, MAP1LC3s and GABARAPs, of integrin β3. Those studies exemplify the utility of motif predictions to guide experimental proposals.…”
Section: Introductionmentioning
confidence: 99%